Sebulir cinta Tuhan / Taufik Al-Hakim; penerjemah, Sulthon Pamungkas, Irfan Zamzani, Muh. Syaifuddin Nur - TAUFIK AL-HAKIM; Sulthon Pamungkas; Irfan Zamzani; Syaifuddin Nur, Muh. (Semesta Ilmu, 2017)
v, 146 hlm. ; 21 cm.